2004
DOI: 10.1258/jrsm.97.2.72
|View full text |Cite
|
Sign up to set email alerts
|

Swallowed partial dentures

Abstract: SUMMARYSwallowed or inhaled partial dentures can present a diagnostic challenge. Three new cases are described, one of them near-fatal because of vascular erosion and haemorrhage. The published work points to the importance of good design and proper maintenance. The key to early recognition is awareness of the hazard by denture-wearers, carers and clinicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…This type of wire-containing dentures has been reported to have higher tendency to impact and perforate in the GI tract. 11 The risk of perforation is increased when ingested dentures contain a broken wire with a sharp pointy end, as in our case (Figure 13). …”
Section: Denturessupporting
confidence: 52%
“…This type of wire-containing dentures has been reported to have higher tendency to impact and perforate in the GI tract. 11 The risk of perforation is increased when ingested dentures contain a broken wire with a sharp pointy end, as in our case (Figure 13). …”
Section: Denturessupporting
confidence: 52%
“…In dental operatory, the ingested foreign body may include teeth, restorations, restorative materials, instruments, rubber dam clamps, gauze packs, and so forth [1][2][3]. Similar case studies have also been reported previously [4]. Grossman [5] determined that 87% of the ingested foreign bodies enter the gastrointestinal tract, and 13% enter the respiratory tract.…”
Section: Introductionmentioning
confidence: 72%
“…However, with the improvement in appearance and wear resistance of the better quality plastic and composite artificial teeth, porcelain teeth are seldom used on dentures in the UK. 4 Despite the many calls for use of radio-opaque denture base materials 5 no such product seems available in the UK. Tsao 6 and Davy 7 investigated the use of materials in dentures to make them radio-opaque, without adversely compromising on the strength of the material, but these were never marketed because of concerns that the halide in the material might have cancer-inducing potential.…”
Section: Discussionmentioning
confidence: 99%
“…Barium swallow is usually one of the early investigation modalities done in patients with swallowing problems. Many authors have quoted a high sensitivity and specifi city of barium study in the detection of ingested foreign bodies 8 whereas others 4 have found it to be unhelpful, making subsequent endoscopy more diffi cult. In our case barium swallow was inconclusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation